The storytelling of male body of a migrant African negro : comparative study of Arabic- and French-language fiction - (:unkn) unknown (My University, 2022)
The narrative of the male body of the African-African migrant. A comparative study of Arabic-speaking and Francophone fictions emerged from the increasingly pressing reality of migration.As an ethno-sociological fact feeding notably on social evolutions and upheavals, the literature reflects the questioning of these populations affected by the migration phenomenon and the inevitable problem of their reconstruction of their identity. It reflects on the difficulties of entering into a heterogeneous and heterocultural space and on the sacrifices they would be willing to make to remedy them and make the link between past and future: how far would they be Ready to renounce their culture, to abandon a part of themselves, to alter their identity, to become new individuals, while preserving the identity and cultural elements of their past?One theme in particular allows us to answer these fundamental questions for migrants: the representation of the physical body varies according to the space in which it is inscribed, and a fortiori, in the context of transplantation in a foreign territory.This question is perhaps even more crucial for African migrants, who are immediately stigmatized by the color of their skin and by different behavior and gesture codes. This is why it seemed interesting to us to devote our thesis to the study of the narration of the male body of African-African migrants in African literature. This study will took into account both the biological aspects of the body and its relations with society, as well as the narrative projects of the authors. It focused on the inscription of the body in the narrative and will aim at identifying the narrative procedures and meanings of the male body.
Keywords: African Research